Perlindungan Hukum terhadap Pekerja yang Memiliki Perjanjian Kerja Tidak Tertulis - Erni Nurdin; Erna Susanti; Setiyo Utomo (Jurnal Hukum Lex Generalis, 2025)
An unwritten employment agreement is a contract made verbally. Although verbal employment agreements do not violate existing laws and regulations, this form of agreement places workers in a vulnerable position. In the city of Samarinda, there are workers employed under unwritten agreements. Legal protection for workers with unwritten employment agreements is regulated by the Labor Law and the Job Creation Law. Workers in Samarinda who are employed under such agreements can seek legal protection by filing a report with the Department of Manpower and Transmigration of East Kalimantan Province.